# Class 11 RD Sharma Solutions – Chapter 30 Derivatives – Exercise 30.3

### Question 1. Differentiate f(x) = x^{4} – 2sinx + 3cosx with respect to x.

**Solution:**

Given that, f(x) = x

^{4}– 2sinx + 3cosxNow, differentiate w.r.t. x, we get

â‡’ d(x

^{4 }– 2sinx + 3cosx) / dxâ‡’ d(x

^{4})/dx – 2.d(sinx)/dx + 3.d(cosx)/dxâ‡’ 4x

^{3}– 2cosx – 3sinx.

### Question 2. Differentiate f(x) = 3^{x} + x^{3} + 3^{3} with respect to x.

**Solution:**

Given that, f(x) = 3

^{x}+ x^{3}+ 3^{3}Now, differentiate w.r.t. x, we get

â‡’

d(3^{x}+ x^{3}+ 3^{3}) / dxâ‡’ d(3

^{x})/dx + d(x^{3})/dx + d(3^{3})/dxâ‡’ 3

^{x}log3 + 3x^{2}+ 0 [As we know, d(a^{x})/dx = a^{x}loga]â‡’ 3

^{x}log3 + 3x^{2}

### Question 3. Differentiate f(x) = x^{3}/3 – 2âˆšx + 5/x^{2} with respect to x.

**Solution:**

Given that, f(x) = x

^{3}/3 – 2âˆšx + 5/x^{2}Now, differentiate w.r.t. x, we get

â‡’

d(x^{3}/3 – 2âˆšx + 5/x^{2}) / dxâ‡’ 1.d(x

^{3})/3dx – 2d(âˆšx)/dx + 5d(x^{-2})/dxâ‡’ 1/3.3x

^{2}– 2.1/2.1/âˆšx + 5(-2) x^{-3}â‡’ x

^{2 }– x^{-1/2 }– 10x^{-3}â‡’ x

^{2 }– 1/âˆšx – 10/x^{3}

### Question 4. Differentiate f(x) = e^{xloga} + e^{alogx} + e^{aloga} with respect to x.

**Solution:**

Given that, f(x) = e

^{xloga}+ e^{alogx}+ e^{aloga}Now, differentiate w.r.t. x, we get

â‡’ d(e

^{xloga}+ e^{alogx}+ e^{aloga})â‡’ d(e

^{xloga})/dx + d(e^{alogx})/dx + d(e^{aloga})/dxâ‡’ e

^{xloga}.loga + e^{alogx}.a/x + 0 [As we know, e^{aloga}is constant]â‡’ loga.e

^{xloga}+ a/x.e^{alogx}â‡’ loga.a

^{x}+ a/x x^{a }[Here, a^{x}can be written as a e^{xloga}]â‡’ a

^{x}loga + ax^{a-1}

### Question 5. Differentiate f(x) = (2x^{2} + 1)(3x + 2) with respect to x.

**Solution:**

Given that, f(x) = (2x

^{2}+ 1)(3x + 2)Now, differentiate w.r.t. x, we get

â‡’

d(2x^{2}+ 1)(3x + 2)/dxâ‡’ (3x + 2)d(2x

^{2}+ 1)/dx + (2x^{2}+ 1)d(3x + 2)/dxâ‡’ (3x + 2)(4x+0) + (2x

^{2}+ 1)(3+ 0)â‡’ (12x

^{2}+ 8x + 6x^{2}+ 3)â‡’ 18x

^{2}+ 8x + 3.

### Question 6. Differentiate f(x) = log_{3}x + 3log_{e}x + 2tanx with respect x.

**Solution:**

Given that, f(x) = log

_{3}x + 3log_{e}x + 2tanxNow, differentiate w.r.t. x, we get

â‡’

d(log_{3}x + 3log_{e}x + 2tanx)/dxâ‡’ 1/log

_{3}d(logx)/dx + 3.d(log_{e}x)/dx + 2.d(tanx)/dxâ‡’ 1/log

_{3 }Ã— 1/x + 3/x + 2sec^{2}xâ‡’ 1/xlog

_{3}+ 3/x + 2sec^{2}x

### Question 7. Differentiate f(x) = (x + 1/x) (âˆšx + 1/âˆšx) with respect to x.

**Solution:**

Given that, f(x) = (x + 1/x) (âˆšx + 1/âˆšx)

Now, differentiate w.r.t. x, we get

â‡’ d((x + 1/x) (âˆšx + 1/âˆšx))/dx

â‡’ (x + 1/x) d(âˆšx + 1/âˆšx)/dx + (âˆšx + 1/âˆšx) d(x + 1/x)/dx

â‡’ (x + 1/x) (1/2âˆšx – 1/2x

^{3/2}) + (âˆšx + 1/âˆšx) (1 – 1/x^{2})â‡’ {x/(2âˆšx) – x/(2x

^{3/2}) + 1/2(x^{3/2})- 1/(2x^{5/2})} + {âˆšx – âˆšx/x^{2}+ 1/âˆšx – 1/x^{5/2}}â‡’ (1.âˆšx/2 – 1/2âˆšx + 1/2x

^{3/2}– 1/2x^{5/2}+ âˆšx – 1/x^{3/2}+ 1/âˆšx – 1/x^{5/2})â‡’ (3âˆšx/2 + âˆšx/2 – 1/2x

^{3/2}– 3/2x^{5/2})â‡’ 3x

^{1/2}/2 + x^{-1/2}/2 – x^{-3/2}/2 – 3x^{-5/2}/2

### Question 8. Differentiate f(x) = (âˆšx + 1/âˆšx)^{3} with respect to x.

**Solution:**

Given that, f(x) = (âˆšx + 1/âˆšx)

^{3}Now, differentiate w.r.t. x, we get

â‡’ d(âˆšx + 1/âˆšx)

^{3 }/dxâ‡’ d(x

^{3/2}+ 3x.1/x + 3âˆšx.1/x + 1/x^{3/2})/dx [As we know that, (a + b)^{3}= a^{2}+ 3a^{2}b + 3ab^{2}+ b^{3}]â‡’ d(x

^{3/2}+ 3x^{1/2}+ 3x^{-1/2}+ x^{-3/2})/dxâ‡’ 3x

^{1/2}/2 + 3x^{-1/2}/2 + 3.(-1/2).x^{-3/2}– 3x^{-5/2}/2â‡’ 3x

^{1/2}/2 – 3x^{-5/2}/2 + 3x^{-1/2}/2 – 3x^{-3/2}/2.

### Question 9. Differentiate f(x) = 2x^{2} + 3x + 4 /x with respect to x.

**Solution:**

Given that, f(x) = 2x

^{2}+ 3x + 4 /xNow, differentiate w.r.t. x, we get

â‡’ d(2x

^{2}+ 3x + 4 /x) / dxâ‡’d(2x

^{2}/x + 3x/x + 4/x) /dxâ‡’ d(2x + 3 + 4x

^{-1}) / dxâ‡’ 2- 4/x

^{2}

### Question 10. Differentiate f(x) = (x^{3}+ 1) (x – 2) / x^{2 }with respect x.

**Solution:**

Given that, f(x) = (x

^{3}+ 1) (x – 2) / x^{2}Now, differentiate w.r.t. x, we get

â‡’ d{(x

^{3}+ 1) (x – 2) / x^{2}} / dxâ‡’ d{(x

^{4}– 2x^{3}+x – 2)/ x^{2}} / dxâ‡’ d(x

^{2}– 2x + x^{-1}– 2x^{-2}) / dxâ‡’ d(x

^{2})/dx – 2d(x)/dx + d(x^{-1})/dx – 2d(x^{-2})/dxâ‡’ 2x – 2 – 1/x

^{2}+ 4/x^{3}â‡’ 2x – 2 – 1/x

^{2}+ 4/x^{3}

### Question 11. Differentiate f(x) = acosx + bsinx + c / sinx with respect to x.

**Solution:**

Given that, f(x) = acosx + bsinx + c / sinx

Now, differentiate w.r.t. x, we get

â‡’ d(acosx + bsinx + c / sinx) /dx

â‡’ a.d(cosx)/dx(sinx) + b.d(1)/dx + c.d/dx(sinx)

â‡’ a(-cosec

^{2}x) + 0 + c(-cosecx.cotx)â‡’ -acosec

^{2}x – c.cosecx.cotx

### Question 12. Differentiate f(x) = (2secx + 3cotx – 4tanx) with respect to x.

**Solution:**

Given that, f(x) = (2secx + 3cotx – 4tanx)

Now, differentiate w.r.t. x, we get

â‡’ d(2secx + 3cotx – 4tanx) / dx

â‡’ 2.d(2secx)/dx + 3.d(cotx)/dx – 4.d(tanx)/dx

â‡’ 2secxtanx – 3cosec

^{2}x – 4sec^{2}x

### Question 13. Differentiate f(x) = (a_{0}x^{n} + a_{1}x^{n-1} + a_{2}x^{n-2 }+ ……… + a_{n-1}x + a_{n}) with respect to x.

**Solution:**

Given that, f(x) = (a

_{0}x^{n}+ a_{1}x^{n-1}+ a_{2}x^{n-2 }+ ……… + a_{n-1}x + a_{n})Now, differentiate w.r.t. x, we get

â‡’ d(a

_{0}x^{n}+ a_{1}x^{n-1}+ a_{2}x^{n-2}+ ……… + a_{n-1}x + a_{n}) / dxâ‡’ a

_{0}d(x)^{n}/dx + a_{1}d(x)^{n-1}/dx + a_{2}d(x)^{n-2}/dx + ………. + a_{n-1}d(x)/dx + a_{n}d(1)/dxâ‡’ na

_{0}x^{n-1}+ (n-1)a_{1}x^{n-2}+ ………. + a_{n-1}+ 0â‡’ na

_{0}x^{n-1}+ (n-1)a_{1}x^{n-2}+ ……….. + a_{n-1}

### Question 14. Differentiate f(x) = 1/sinx + 2^{x+3} + 4/logx^{3 }with respect to x.

**Solution:**

Given that, f(x) = 1/sinx + 2

^{x+3}+ 4/logx^{3 }Now, differentiate w.r.t. x, we get

â‡’ d/dx (1/sinx + 2^{x+3}+ 4/logx^{3})â‡’ d(cosecx)/dx + 2

^{3}d(2^{x})/dx + 4/log3 Ã— d(logx)/dx [As we know that, log_{b}a = loga/logb]â‡’ -cosecx.cotx + 8 Ã— 2log2 + 4/log3 Ã— 1/x [Since, d(a

^{x})/dx = a^{x}loga]â‡’ -cosecx.cotx + 2

^{x+3}log2 + 4/xlog3

### Question 15. Differentiate f(x) = (x + 5)(2x – 1) / x with respect to x.

**Solution:**

Given that, f(x) = (x + 5)(2x – 1) / x

Now, differentiate w.r.t. x, we get

â‡’ d/dx {(x + 5)(2x

^{2 }– 1)/x}â‡’ d/dx (2x

^{3}+ 10x^{2}– x – 5 / x)â‡’ d(2x

^{2}+ 10x – 1 – 5x^{-1})/dxâ‡’ 2d(x

^{2})/dx + 10d(x)/dx – d(1)/dx – 5d(x^{-1})/dxâ‡’ 2.2x + 10 – 0 + 5/x

^{2}â‡’ 4x + 10 + 5/x

^{2 }

### Question 16. Differentiate f(x) = log(1/âˆšx) + 5x^{a} – 3a^{x} + 3âˆšx^{2} + 6(^{4}âˆšx^{-3}) with respect to x.

**Solution:**

Given that, f(x) = log(1/âˆšx) + 5x

^{a}– 3a^{x}+ 3âˆšx^{2}+ 6(^{4}âˆšx^{-3})Now, differentiate w.r.t. x, we get

â‡’ d/dx {log(1/âˆšx) + 5x

^{a}– 3a^{x}+^{3}âˆšx^{2}+ 6(^{4}âˆšx^{-3})}â‡’ d(log(1/âˆšx)/dx + 5d(x

^{a})/dx – 3(a^{x}) + d(^{3}âˆšx^{2})/dx + 6d(^{4}âˆšx^{-3})/dxâ‡’ -1/2.1/x + 5ax

^{a-1}– 3a^{x}loga + 2x^{-1/3}/3 + 6x^{-7/4}(-3/4)â‡’ -1/2x + 5ax

^{a-1}– 3a^{x}loga + 2x^{-1/3}/3 – 9x^{-7/4}/2

### Question 17. Differentiate f(x) = cos(x + a) with respect to x.

**Solution:**

Given that, f(x) = cos(x + a)

Now, differentiate w.r.t. x, we get

â‡’ d{cos(x + a)}/dx

â‡’ d(cosx.cosa – sinx.sina)/dx

â‡’ cosa.d(cosx)/dx – sina.d(sinx)/dx

â‡’ cosa(-sinx) – sina(cosx)

â‡’ cosx.sina + sinx.cosa

â‡’ -(sinx.cosa + cosx.sina)

â‡’ -sin(x + a)

### Question 18. Differentiate f(x) = cos(x – 2)/sinx with respect to x.

**Solution:**

Given that, f(x) = cos(x – 2)/sinx

Now, differentiate w.r.t. x, we get

â‡’ d{cos(x – 2)/sinx)/dx

â‡’ d{(cosx.cos2 + sinx.sin2)/sinx} / dx

â‡’ cos2.d(cotx)/dx + sin2.d(1)/dx

â‡’ -cos2.cosec

^{2}x + 0â‡’ -cosec

^{2}x.cos2

### Question 19. If y = {sin(x/2) + cos(x/2)}, find dy/dx at x = Ï€/6.

**Solution:**

Given that, y = {sin(x/2) + cos(x/2)} …..(1)

Find that dy/dx at x = Ï€/6

Now, differentiate eq(1) on both side w.r.t. x, we get

dy/dx =d{sin(x/2) + cos(x/2)}/dxâ‡’ d{sin

^{2}(x/2) + cos^{2}(x/2) + 2sin(x/2).cos(x/2)}/dxâ‡’ d(1 + sinx)/dx [As we know that sin

^{2}x + cos^{2}x = 1]â‡’ 0 + cosx [As we know that sin

^{2}x= 2sinx.cosx]â‡’ cosx

Now put x = Ï€/6

â‡’ cos(Ï€/6)

â‡’ âˆš3/2

### Question 20. If y = (2 – 3cosx / sinx), find dy/dx at x = Ï€/4.

**Solution:**

Given that, y = (2 – 3cosx / sinx) ….(1)

Find that dy/dx at x = Ï€/4

Now, differentiate eq(1) on both side w.r.t. x, we get

dy/dx =d(2 – 3cosx / sinx) / dxâ‡’ d(2cosecx – 3cotx) / dx

â‡’ 2d(cosecx)/dx – 3d(cotx)/dx

â‡’ -2cosecx.cotx + 3cosec

^{2}xNow put x = Ï€/4

â‡’ -2cosec(Ï€/4).cot(Ï€/4) + 3cosec

^{2}(Ï€/4)â‡’ -2âˆš2 – 1 + 3.2

â‡’ -2âˆš2 + 6

â‡’ 6 – 2âˆš2

### Question 21. Find the slope of the tangent to the curve f(x) = 2x^{6} + x^{4} – 1 at x = 1.

**Solution:**

Given that f(x) = 2x

^{6}+ x^{4}– 1 at x = 1.Find the slope of the tangent at a point x = 1

Now, differentiate w.r.t. x, we get

â‡’ d(2x

^{6}+ x^{4}-1)/dxâ‡’ 2dx

^{6}/dx + dx^{4}/dx – d.1/dxâ‡’ 12x

^{5}+ 4x^{3}– 0â‡’ 12x

^{5}+ 4x^{3}Now put x = 1

â‡’ 12(1)

^{5}+ 4(1)^{3}â‡’ 12 + 4

â‡’ 16

Hence, the slope of the tangent to the curve f(x) at x = 1 is 16.

### Question 22. If y = âˆšx/a + âˆša/x, prove that 2xy.dy/dx = (x/a – a/x)

**Solution:**

Given that, y = âˆšx/a + âˆša/x

Prove that 2xy.dy/dx = (x/a – a/x)

Proof:

dy/dx = d(âˆšx/a + âˆša/x)/dxâ‡’ 1/âˆša.d(âˆšx)/dx + âˆša.d(1/âˆšx)/dx

â‡’ 1/âˆša.1/2âˆšx + âˆša(-1/2).1/xâˆšx

â‡’ 1/2x{âˆšx/a + (-âˆša/x)}

â‡’ 2x.dy/dx = âˆšx/a – âˆša/x

Multiplying both side by y = âˆšx/a + âˆša/x, we get

â‡’ 2xy.dy/dx = (âˆšx/a – âˆša/x)(âˆšx/a + âˆša/x)

â‡’ (x/a – a/x)

Hence proved.

### Question 23. Find the rate at which function f(x) = x^{4} – 2x^{3} + 3x^{2} + x + 5 changes with respect to x.

**Solution:**

Given that, f(x) = x

^{4}– 2x^{3}+ 3x^{2}+ x + 5Now, differentiate w.r.t. x, we get

df(x)/dx = d(x^{4}– 2x^{3}+ 3x^{2}+ x + 5) / dxâ‡’ 4x

^{3}– 6x^{2}+ 6x + 1.

### Question 24. If y = 2x^{9}/3 – 5x^{7}/7 + 6x^{3} – x, find dy/dx at x = 1.

**Solution:**

Given that, y = 2x

^{9}/3 – 5x^{7}/7 + 6x^{3}– x …..(1)Find that dy/dx at x = 1

Now, differentiate eq(1) on both side w.r.t. x, we get

dy/dx = d(2x^{9}/3 – 5x^{7}/7 + 6x^{3}– x) / dxâ‡’ 2/3dx

^{9}/dx – 5/7dx^{7}/dx + 6dx^{3}/dx – dx/dxâ‡’ 2/3.9x

^{8}– 5/7.7x^{6}+ 18x^{2}– 1â‡’ 6x

^{8}– 5x^{6}+ 18x^{2}– 1.Put x = 1

â‡’ 6(1)

^{8}– 5(1)^{6}+ 18(1)^{2}– 1â‡’ 6 – 5 + 18 – 1

â‡’ 18

### Question 25. If f(x) = Î»x^{2} + Î¼x + 12, f'(4) = 15 and f'(2) = 11, then find Î» and Î¼.

**Solution:**

Given that, f(x) = Î»x

^{2}+ Î¼x + 12 …..(1)f'(4) = 15 and f'(2) = 11

Find: the value of Î» and Î¼.

Now, differentiate eq(1) w.r.t. x, we get

f(x) = Î»x

^{2}+Î¼x + 12f'(x) = 2Î»x + Î¼

Now put f'(4) = 15, we get

â‡’ 2Î»(4) + Î¼ = 15

â‡’ 8Î» + Î¼ = 15 ……………(1)

Now put, f'(2) = 11

â‡’ 2Î»(2) + Î¼ = 11

4Î» + Î¼ = 11 …………… (2)

From equation (1) and (2), we get

â‡’ 4Î» = 4

â‡’ Î» = 1

Now put value of Î» in equation (1), we get

â‡’ 8(1) + Î¼ = 15

â‡’ Î¼ = 7

Hence, the value of Î» = 1 and Î¼ = 7

â€‹

### Question 26. For the function f(x) = x^{100}/100 + x^{99}/99 + ………….. + x^{2}/2 + x + 1.

### Prove that f'(1) = 100f'(0).

**Solution:**

Given that, f(x) = x

^{100}/100 + x^{99}/99 + ………….. + x^{2}/2 + x + 1Now, differentiate w.r.t. x, we get

â‡’ f'(x) = x

^{99}+ x^{98}+ ………… + x + 1 + 0 ……………..(1)From equation (1),

â‡’ f'(1) = 1 + 1 + …………….(100 times)

â‡’ 100

Again,

â‡’ f'(0) = 0 + 0 + ………….. + 1

â‡’ 1

Now,

â‡’ f'(1) = 100

â‡’ 100 Ã— 1 = 100 Ã— f'(0)

â‡’ f'(1) = 100f'(0)

Hence Proved

## Please

Loginto comment...